Arbitrary withholding of consent to humanitarian relief in non-international armed conflict : legal regulations and consequences - Veerakatty, Vijitha (International humanitarian law series ;, 2024)
"How to legally assess the situation when humanitarian actors in non-international armed conflicts are arbitrarily denied access to the affected civilian population? This book answers this question from the perspective of the five main actors involved in humanitarian relief in non-international armed conflicts: the affected State, non-State armed groups, humanitarian actors, non-belligerent States, and the affected civilian population. It examines the legal regulations and consequences for each of these actors. In doing so, the book not only draws attention to existing legal gaps and challenges, but also encourages readers to rethink outdated legal concepts and discuss new approaches"--